2007
DOI: 10.21273/hortsci.42.5.1157
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fertigation in ‘Manzanilla de Sevilla’ Olive Oil Quality

Abstract: We report the results of a study carried out in a ‘Manzanilla de Sevilla’ olive orchard near Seville, Spain, where the influence of different fertigation treatments on oil chemical composition was considered. Four treatments were established: control (no fertilizer) and T200, T400, and T600 in which each tree, respectively, received 200, 400, or 600 g N per irrigation season of a 4N–1P–3K complex fertilizer applied daily from 1999 to 2003. Results shown here correspond to the last 2 years of the experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
56
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 33 publications
13
56
3
Order By: Relevance
“…This could have accounted for the observed increase in canopy volume, flower quantity, fruit number per tree and fruit weight with the amount of fertilizer. These conclusions are further evidence to confirm those reported in the two related papers made with the same experimental design (Morales-Sillero et al 2007, 2008. For these growing conditions and when the fruits are used for oil production, then T400 (460 g N per tree, the 400 g of the treatment plus the 60 g supplied by the irrigation water) could be the most adequate treatment; if the fruits are for table olive production, the T600 treatment (660 g N per tree, the 600 g of the treatment plus the 60 g supplied by the irrigation water) could be the most appropriate for the producer, but there is a risk of leaching losses and the possibility of groundwater contamination.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This could have accounted for the observed increase in canopy volume, flower quantity, fruit number per tree and fruit weight with the amount of fertilizer. These conclusions are further evidence to confirm those reported in the two related papers made with the same experimental design (Morales-Sillero et al 2007, 2008. For these growing conditions and when the fruits are used for oil production, then T400 (460 g N per tree, the 400 g of the treatment plus the 60 g supplied by the irrigation water) could be the most adequate treatment; if the fruits are for table olive production, the T600 treatment (660 g N per tree, the 600 g of the treatment plus the 60 g supplied by the irrigation water) could be the most appropriate for the producer, but there is a risk of leaching losses and the possibility of groundwater contamination.…”
Section: Discussionsupporting
confidence: 91%
“…They found that the greater fruit yield of the fertigation treatment with respect to the control, irrigated without fertilizer, resulted from an increase in fruit number but not in fruit weight. The increase in fruit weight recorded in this work could have been due, at least in part, to increased fruit K concentration: results obtained by Morales-Sillero et al (2007) from a research carried out in the same orchard, suggested that the accumulation of K induced osmotic adjustment in the fruit cells, which enhance water accumulation, leading to an increase in fruit weight.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…[37], Prunus amygdalus Batsch [38], Brassica napus L. [39], Nigella sativa Linn. [40] and Olea europaea L. [41][42][43]. J. curcas can reproduce through self-and cross-pollination and is pollinated by insects [44] but which pollinators [45] and which pollination mode yields the highest oil quantity and best oil quality has not been studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…Suitable rate of the fertilizers should be used for the highest protein and oil contents of oilseed (Kumar et al 2006). Morales-Sillero et al (2007) reported that oil content of olive is unaffected but fatty acid composition is affected by the N fertilization treatment. Fertilizer treatments accelerate oil fruit ripening, increase oil contents and change the fatty acid composition of the oil fruits.…”
Section: Introductionmentioning
confidence: 99%